Constituintes químicos das flores de Pterogyne nitens (Caesalpinioideae) - Regasini, Luis Octávio [UNESP]; Fernandes, Daniara Cristina [UNESP]; Castro-Gamboa, Ian [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Furlan, Maysa [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Barreiro, Eliezer Jesus; Cardoso-Lopes, Elaine Monteiro; Young, Maria Cláudia Marx; Torres, Luce Brandão; Vellosa, José Carlos Rebuglio; Oliveira, Olga Maria Mascarenhas de (Sociedade Brasileira de Química, 2008)
The phytochemical investigation of the flowers of Pterogyne nitens (Caesalpinioideae) resulted in the isolation and identification of nine phenolic derivatives, quercetin 3-O-sophoroside, taxifolin, astilbin, ourateacatechin, caffeic, ferulic, sinapic, chlorogenic and gallic acid, besides two guanidine alkaloids, pterogynine, pterogynidine. This is the first time these compounds have been reported in P. nitens flowers. As this is a monospecific genus, these secondary metabolites may have taxonomical significance. Their structures were assigned on the basis of spectroscopic analyses, including two-dimensional NMR techniques.
Chemical constituents of the flowers of Pterogyne nitens (caesalpinioideae)
Keywords: Pterogyne nitens; flavonoids; guanidine alkaloids